Embodiment and Disorientation: A Phenomenological Analysis of Work from Home During COVID-19 - Aggarwal, Neha; Todariya, Saurabh; Trehan, Kriti (Human studies, 2024)
Working from home (WFH) is a new reality and norm in today’s work culture. COVID-induced lockdown introduced the concept of WFH for many people. Blurring home and workplace boundaries was a prominent cause of disorientation in people’s lives. Hence, WFH becomes a significant phenomenon to explore as it raises the fundamental question of body and space in shaping people’s experiences. To study this, the researchers designed a phenomenological inquiry and examined the lived phenomenon of WFH during the COVID lockdown. Borrowing theoretical concepts from philosophers Martin Heidegger and Merleau-Ponty, they aimed to understand human experiences from an embodied perspective. They interviewed a few adults (age group 27–50) in three urban Indian cities during the first phase of the COVID-19 lockdown. The participants’ experiences were transcribed, and Interpretative Phenomenological Analysis (IPA) was conducted. The IPA themes highlighted their varied lived experiences and lifeworld, such as distractions in working from home, their changed routines, habits, and social interaction. The findings are discussed through phenomenological psychology concepts such as embodied cognition, body memory, extended self, shared empathy, intersubjectivity and pre-reflective bodily intelligence in coping. The study’s contribution is that it advances a methodological understanding by interpreting people’s experiences from a phenomenological view of being-in-the-world in which the individual is not an isolated entity but is in the world/placed in the world with other people and the environment.